As regiões montanhosas e o planejamento de suas paisagens: proposta de zoneamento ambiental para a Mantiqueira meridional mineira - Roberto Marques Neto (Confins)
In the tropical Atlantic domain the most intense interpenetration between zonal and azonal elements occur in the mountainous landscapes defining its structure and functionality with regional geosystems which mix forestry belts over loamy and well-developed soils with rupestrian fields and uplands over shallow and rich in prime minerals soils that occur in geomorphologic regions such as Serra da Mantiqueira. The tropical mountains of the southeast Brazil present, therefore, peculiar landscapes provided of specific capabilities to the handling, so that proposals for environmental planning in regional scale must start from an integrated study of these landscapes in a way that takes into account the specificities of the regional geosystems. From such premises the present work presents a proposal of environmental zoning for the portion of Southern Mantiqueira of Minas Gerais established from a dialogical approach between the geosystemic conception and the landscape ecology.